Bioelectrical impedance analysis to define an excess of body fat: evaluation in patients with psoriasis. (19th May 2017) - Galluzzo, M.; Talamonti, M.; Perino, F.; Servoli, S.; Giordano, D.; Chimenti, S.; De Simone, C.; Peris, K.
Abstract: Background: There is strong evidence that obesity is closely associated with psoriasis. However, data on body composition are lacking in psoriasis. The purpose of this study were to investigate the body composition in psoriasis patients using bioelectrical impedance analysis and to correlate the bioelectrical impedance data with disease severity and laboratory parameters. Methods: Anthropometric measurements and bioelectrical impedance analyses were performed on patients with psoriasis, naïve to any systemic treatment, who attended the outpatient clinics of two University centers. Results: Data of 164 adult patients were analyzed. Compared to men, women had several significantly higher bioelectrical impedance parameters including reactance, fat mass% and adipose tissue%. The values of adipose tissue were positively correlated only with patients age ( p = .021) and age at disease onset ( p = .0006), but not with disease severity. In addition, we observed that the use of BMI cutoffs allowed to categorize 36.7% of women and 19.2% of men as obese, while fat mass% showed that 53.3% of women and 48.1% of men were obese. Conclusion: In our study, psoriasis is been associated with a high fat mass%. We suggest that screening for body fat distribution in psoriatic patients might be useful to identify early obesity-related disease.